Selectivity in feeding preferences and ranging patterns in spider monkeys Ateles geoffroyi yucatanensis of northeastern Yucatan peninsula, Mexico - Carmen SCHERBAUM, Alejandro ESTRADA (Current Zoology, 2013)
The spider monkey, a fruit specialist and important seed dispersal agent in the Neotropics, is an endangered primate due to habitat loss, hunting and the pet trade. Spider monkeys have been the subject of a few studies in Central and South America, but little is known about the diet and ranging for this primate in southern Mexico. Here we report the results of a six-month long study (October 2010 to March 2011) of the feeding preferences and ranging patterns of the Yucatan spider monkey Ateles geoffroyi yucatanensis living in the “Ya´ax´che” reserve by the Caribbean coast in northeast Yucatan peninsula. Focal animal and scan sampling as well as GPS tracking were used to document spider monkey feeding behavior, location of food trees and ranging in the reserve. The spider monkeys used 36 species of plants (94% trees; n = 432) and six non tree morphospecies as a source of food. Six tree species accounted for ≥80% of total feeding time and for 74% of all trees used. Fruits accounted for 59% of total feeding time, followed by leaves (35%), palm piths (5%) and other plant parts (1%). Total range used by the monkeys was estimated at 43% of semievergreen rainforest habitat available (ca 40ha). Range use was not random with segments showing light, moderate and heavy use; the use of different areas of their range varied monthly and was closely linked to the spatial dispersion of the trees used for food [Current Zoology 59 (1): 125–134, 2013].